Emerging perspectives on once-weekly insulins in type 1 and type 2 diabetes: a mini-review - Denimal, Damien (Frontiers in Endocrinology, 2025)
The development of once-weekly basal insulin analogues, such as insulin icodec and efsitora alfa, represents a promising strategy to reduce injection burden and improve adherence in diabetes management. This mini-review summarizes the recent findings from clinical trials evaluating once-weekly insulin therapies in both type 1 and type 2 diabetes. In type 1 diabetes, available data remain limited; however, the ONWARDS 6 and QWINT-5 trials demonstrated that once-weekly icodec and efsitora, respectively, achieved comparable reductions in HbA1c to once-daily insulin degludec, when used in combination with prandial insulin. In type 2 diabetes, accumulating evidences from randomized clinical trials supports the efficacy of once-weekly icodec and efsitora, showing non-inferiority—and in some cases, superiority—compared to once-daily basal insulin, both in insulin-naïve individuals and in those previously treated with insulin. Safety profiles of once-weekly insulins in type 2 diabetes are reassuring, with similar rates of clinically significant and severe hypoglycemia compared to once-daily regimens. In contrast, trials in type 1 diabetes reported higher hypoglycemia rates with once-weekly insulins. Recent findings from the COMBINE program demonstrated that the fixed-ratio combination of icodec and semaglutide (IcoSema) produced superior HbA1c reductions compared to either agent alone, though not superior to a basal-bolus regimen with glargine and aspart insulin. However, several important questions remain to be addressed regarding once-weekly insulins, including their long-term efficacy on cardiovascular outcomes and overall long-term safety.